Assessing Post Traumatic Stress Disorder (PTSD) and Evaluating Gratitude-Based Coping Strategies for Caregivers of Pediatric Cancer Patients. - Bashir, Noman; Khan, Mustajab Ahmad; Ikram, Sadia; Hassan, Muhammad Sabbih ul; Siddiqui, Raima; Rafaqat, Nida (Journal of Postgraduate Medical Institute, 2025)
Objective:The current study focuses on the frequency and severity of post-traumatic stress disorder (PTSD) in caregivers of children with cancer and the relationship between PTSD symptoms and the caregivers' level of gratitude in Pakistan. Methodology: This Cross-sectional design research was carried out between January 2023 and March 2023 at the Department of Oncology in Shaukat Khanum Memorial Cancer Hospital & Research Centre, Peshawar, Northwest General Hospital & Research Centre, Peshawar in Khyber Pakhtunkhwa (KPK), and Pakistan Institute of Medical Sciences, Quaid-e-Azam International Hospital in Islamabad, Pakistan.The research included 153 individuals who provided care for children with cancer between the ages of 0 and 12. The selection of these subjects was done using purposive convenience sampling. The PTSD Checklist-Civilian Version (PCL-C) was employed to evaluate the presence of PTSD, while gratitude was quantified using the Gratitude Questionnaire-Six-Item Form (GQ-6). The data were examined using the statistical software SPSS V28, utilizing descriptive statistics, independent t-tests, and Pearson's correlation coefficient. Results:The findings showed that 52.94% of caregivers had high levels of PTSD and that severe PTSD symptoms were more common among female caregivers and caregivers with lower educational attainment. Mostly, caregivers expressed moderate (40.52%) or low (30.71%) levels of gratitude. Higher degrees of gratitude were linked to lower levels of PTSD symptoms, according to a statistically significant negative correlation (r = -0.433, p < 0.001) between the two variables. Conclusion:The study emphasizes the possibility of gratitude to shield caregivers of pediatric cancer patients from experiencing or lessening the occurrence and intensity of PTSD symptoms. The results underscore the importance of implementing interventions that focus on the mental well-being of caregivers. Additionally, it is crucial to develop gratitude-based therapies that are specifically tailored for this group in order to enhance their ability to cope with challenges and reduce the overall burden of caregiving.